Improving Student Learning Outcomes in Aqidah Akhlak Learning through the Card Sort Method at MI Darul Ulum Kenongo - Kuryanto; Laila Safitri (Journal of Action Research in Islamic Education, 2025)
This study aims to improve the learning outcomes of the subject of Akidah Akhlak in grade IV students of MI Darul Ulum Kenongo through the application of the Card Sort learning method. The background of this study is the low learning outcomes of students in the subject of Akidah Akhlak, which is indicated by the lack of learning motivation and student activity during the learning process. This study is a classroom action research (CAR) carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were all 20 students of grade IV MI Darul Ulum Kenongo. The Card Sort method was chosen because it emphasizes direct student activity in grouping cards according to material categories, thus encouraging active student involvement in learning. The results of the study showed an increase in learning outcomes from an average pre-cycle score of 72 with a completion rate of 60%, to 78.5 in cycle I (completion 80%), and increased again to 79.5 in cycle II with a completion rate reaching 90%. In addition, there was an increase in student motivation and activeness during the learning process. Thus, the application of the Card Sort method has proven effective in improving students' learning outcomes of Akidah Akhlak. This study recommends the use of active learning methods such as Card Sort as an alternative learning strategy, especially in building character and improving students' understanding of Islamic values, especially during the fasting month.